THE EFFECT OF SOCIAL MEDIA MARKETING ON GAMIFICATION AND WILLINGNESS TO PAY A PREMIUM A GENERATIONAL DIFFERENCES - Tri Tata Wilia; Pristiyanilicia Putri; Arika Juwita Z; Weri Sirait; Havid Syafwan (Smart Education, 2026)
Abstract: This study investigates the influence of social media marketing on gamification and the willingness to pay premiums, specifically within the context of